How to assess ankle osteoarthritis: comparison of the Kellgren and Lawrence scale with functional outcome and digital image analysis - Holzer, Nicolas; Salvo, Davide; Marijnissen, Anne Karien; Che Ahmad, Aminudin; Sera, Emanuele; Hoffmeyer, Pierre; Lübbeke Wolff, Anne; Assal, Mathieu (British Editorial Society of Bone & Joint Surgery, 2012)
Introduction Currently, a validate scale of ankle osteoarthritis (OA) is not available and different classifications have been used, making comparisons between studies difficult. In other joints as the hip and knee, the Kellgren-Lawrence (K&L) scale, chosen as reference by the World Health Organizations is widely used to characterize OA. It consists of a physician based assessment of 3 radiological features: osteophyte formation, joint space narrowing and bone end sclerosis described as follows: grade 0: normal joint; grade 1: minute osteophytes of doubtfull significance; grade 2: definite osteophytes; grade 3: moderate diminution of joint space; grade 4: joint space greatly impaired, subchondral sclerosis. Until now, the K&L scale has never been validated in the ankle. Our objective was to assess the usefulness of the K&L scale for the ankle joint, by determining its reliability and by comparing it to functional scores and to computerized minimal joint space width (minJSW) and sclerosis measurements. Additionally we propose an atlas of standardized radiographs for each of the K&L grades in the ankle.